Slope stability analysis and stabilization new methods and insight - Cheng, Y. M.; Lau, C. K. (CRC Press/Taylor & Francis, 2014)
This book provides a critical review of these and offers several more appropriate approaches for overcoming numerical convergence and the location of critical failure surfaces in two-dimensional and three-dimensional cases.